4,4′-[(1,3,4-Thiadiazole-2,5-diyl)bis(thiomethylene)]dibenzonitrile - Wang, Wenxiang (International Union of Crystallography, 2008)
The title molecule, C(18)H(12)N(4)S(3), consists of three essentially planar fragments, viz. two methyl-substituted benzonitrile rings and a substituted thiadiazole ring. The dihedral angles between the substituted benzonitrile rings and the central thiadiazole ring are 28.29 (10) and 78.83 (6)°, and the dihedral angle between the two benzonitrile rings is 72.89 (7)°.